2019
DOI: 10.1073/pnas.1816585116
|View full text |Cite
|
Sign up to set email alerts
|

AWZ1066S, a highly specific anti- Wolbachia drug candidate for a short-course treatment of filariasis

Abstract: SignificanceOnchocerciasis (river blindness) and lymphatic filariasis (elephantiasis) are neglected tropical diseases that cause severe disability and affect more than 157 million people globally. Current control efforts are hindered by the lack of a safe macrofilaricidal drug that can eliminate the parasitic adult nematodes safely. A clinically validated approach for delivering macrofilaricidal activity is to target the Wolbachia bacterial endosymbiont of the causative nematodes. This first-in-class and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 31 publications
3
73
0
Order By: Relevance
“…Wolbachia titers were reduced by >95% in female worms from rifampicin treated animals at the 1-week timepoint compared to those of worms from vehicle animals. The extensive reduction of Wolbachia titers in adult worms has been previously described in other rodent studies with filarial worms, but the studies were terminated 16-18 weeks post-treatment [26,27,29,40,50], and the long-term effects of antibiotic treatment on filarial worms and their Wolbachia were not evaluated in these models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolbachia titers were reduced by >95% in female worms from rifampicin treated animals at the 1-week timepoint compared to those of worms from vehicle animals. The extensive reduction of Wolbachia titers in adult worms has been previously described in other rodent studies with filarial worms, but the studies were terminated 16-18 weeks post-treatment [26,27,29,40,50], and the long-term effects of antibiotic treatment on filarial worms and their Wolbachia were not evaluated in these models.…”
Section: Discussionmentioning
confidence: 99%
“…Major efforts to identify new drugs to treat the adult stage (macrofilariae) of Onchocerca volvulus have led to the discovery of novel anti- Wolbachia compounds. These studies demonstrated that their respective anti- Wolbachia compounds significantly reduced Wolbachia titers in worms from animals treated with short courses of quinazolines and Tylosin analogs after 16–18 weeks post-first dose [ 26 , 27 , 29 , 40 , 50 ]. In addition, a one-week combination treatment of rifampicin and albendazole resulted in a greater than 99% reduction in Wolbachia levels in B .…”
Section: Discussionmentioning
confidence: 99%
“…Other anti-Wolbachia drugs that have been trialed in humans include rifampicin and moxifloxacin [108] (results yet to be published), and minocycline [109]. Other compounds screened by A•WOL that have shown great promise in pre-clinical development, are high-dose rifampicin [110], rifampicin plus albendazole [111], and an optimized azaquinazoline (AWZ1066S) [112]. Other compounds (in the Drugs for Neglected Diseases initiative (DNDi) filariasis portfolio) [113] include oxfendazole (for which a phase I trial is being planned through the Helminth Elimination Platform (HELP)), emodepside (nearing phase II trial in Ghana for safety, tolerability, and dose/regimen selection), and TylAMac TM (ABBV-4083, developed by A•WOL in partnership with AbbVie [114]), for which a phase II proof-ofconcept trial is being prepared in the DRC [113].…”
Section: Other Compounds In Clinical Developmentmentioning
confidence: 99%
“…In areas hypoendemic for onchocerciasis and co-endemic with loiasis at ≥20% prevalence, MDA is not advisable [13], but after establishing safe dosage and thresholds of L. loa microfilaremia levels [118], moxidectin could be used in TNT modalities of delivery that may potentially be more effective than using ivermectin (due to the enhanced curtailing of transmission that would result from more prolonged suppression of microfilaridermia). Doxycycline (already available) and other anti-Wolbachia macrofilaricides (in pre-clinical and clinical development [110][111][112][113][114]) offer an exciting prospect, as TTd for the former, and ideally with much shorter treatment courses for the latter, albeit requiring high rates of O. volvulus screening, therapeutic coverage, and adherence [107]. Large-scale and long-term (at least 14 years) larviciding of vector breeding sites was effective for vector control in the OCP [1] but unlikely to be implemented elsewhere.…”
Section: Expert Opinionmentioning
confidence: 99%
“…In contrast, Wolbachia -infected filarial nematodes require their Wolbachia endosymbionts for survival, with Wolbachia depletions causing defects in proper nematode development and reproduction, eventually leading to host death ( Slatko et al 2010 ; Landmann et al 2011 ; Taylor et al 2010 ). As such, antibiotics can be used to treat nematode diseases such as lymphatic filariasis and onchocerciasis ( Taylor et al 2014 ; Taylor et al 2005 ; Clare et al 2019 ; Hong et al 2019 ; von Geldern et al 2019 ; Jacobs et al 2019 ; Taylor et al 2019 ).…”
mentioning
confidence: 99%